O34-4 Frailty, pre-frailty and employment outcomes in the health and employment after fifty (HEAF) study. (1st September 2016) - Palmer, Keith; D'Angelo, Stefania; Harris, E Clare; Linaker, Cathy; Gale, Catharine R; Syddall, Holly; Staa, Tjeerd Van; Cooper, Cyrus; Sayer, Avan Aihie; Coggon, David; Walker-Bone, Karen
Abstract : Background: Demographic changes in developed countries are requiring people to work longer. No previous studies, however, have focussed on whether the "frailty" syndrome (which predicts falls, hospitalisations, institutional care, dependency, and mortality in the elderly) causes difficulties in employment. To provide information, we assessed relationships in a population-based cohort of 50-64 year-olds from the HEAF study. Methods: Subjects, who were recruited from 24 English general practices, completed a baseline postal questionnaire on pre-frailty and frailty and several work outcomes, including health-related job loss (HRJL), prolonged sickness absence (>20 days vs. less, past 12 months), having to cut down substantially at work and difficulty coping with work's demands. Associations were assessed using logistic regression. Also, we calculated population attributable fractions (PAFs), representing the proportion of the population burden that is potentially preventable, assuming that risk factors are causal and can be eliminated. Results: In all, 3.9% of 8, 095 eligible respondents were classed as frail and 31.6% as pre-frail. Three-quarters of the former were not in work, while 60% had left their last job on health grounds (odds ratio (OR) for HRJL, vs. non-frail subjects, 30.0 (95% Confidence Interval 23.0–39.2). Among those in work, ORs for prolonged sickness absence, cutting down substantially at work and struggling with work's physical demands were 10.7 (95% CI: 6.5–17.7), 17.2 (95% CI: 10.5–28.4) and 14.8 (95% CI: 8.2–26.6) respectively. The PAF for HRJL when any frailty marker was present was 51.8% and that for prolonged sickness absence was 32.5%. Associations were strongest with slow reported walking speed. Several associations were stronger in manual workers than in managers. Conclusions: Frailty and pre-frailty are not uncommon in 50–64 year-olds. Both are very strongly linked with adverse and economically important employment outcomes. In particular, features of frailty may contribute importantly to HRJL and represent an important target for prevention.